Development and validation of HPLC and CE methods for simultaneous determination of amlodipine and atorvastatin in the presence of their acidic degradation products in tablets - Hassan Said A.; Elzanfaly Eman S.; El-Zeany Salem Badr A.; Salem Maissa Y. (Acta Pharmaceutica)
Two methods were developed for separation and quantitation of amlodipine (AML) and atorvastatin (ATV) in the presence of their acidic degradation products. The first method was a simple isocratic RP-HPLC method while the second was capillary electrophoresis (CE). Degradation products were obtained by acidic hydrolysis of the two drugs and their structures were elucidated for the first time by IR and MS spectra. Degradation products did not interfere with the determination of either drug and the assays were therefore stability-indicating. The linearity of the proposed methods was established over the ranges 1-50 μg mL-1 for AML and ATV in the HPLC method and in the range of 3-50 and 4-50 μg mL-1 for AML and ATV, respectively, in the CE method. The proposed methods were validated according to ICH guidelines. The methods were successfully applied to estimation of AML and ATV in combined tablets.